Curing Behavior of Resorcinol Formaldehyde Resin Adhesives in Mangium and Pine Woods Bonding System under Various Curing Times - Eka M. Alamsyah; Masaaki Yamada; Kinji Taki (Masyarakat Peneliti Kayu Indonesia, 2010)
Effects of room-temperature curing time on the curing behavior of resorcinol formaldehyde (RF) resin adhesives by using thermo mechanical analysis spring method in relation to the mangium (Acacia mangium) and pine (Pinus merkusii) woods bonding system were examined. Total amount of liquid resin adhesives that inserted into the small wire spring was 10 mg for each curing time parameters. Results showed that the curves of modulus of elasticity (E’) from resin adhesives that cured for 1 month, 2 months and 3 months was almost flat from room temperature to 200°C. By far E’ curve of resin adhesives that cured for 3 months did not changed and adhesive predicted had cured completely. Results further showed that in A. mangium and P. merkusii bonding system all laminates bonded with RF in room temperature at least 1 month curing time is required to meet high bond strength with minimally 60 percent wood failure as one of requirements of good bonding performance classification.